Programmed cell death controlled by ANAC033/SOMBRERO determines root cap organ size in arabidopsis - Fendrych, Matyáš; Krebs, Melanie; Schumacher, Karin (Current biology, 2014)
Summary Background The root cap is a plant organ that ensheathes the meristematic stem cells at the root tip. Unlike other plant organs, the root cap shows a rapid cellular turnover, balancing constant cell generation by specific stem cells with the disposal of differentiated cells at the root cap edge. This cellular turnover is critical for the maintenance of root cap size and its position around the growing root tip, but how this is achieved and controlled in the model plant Arabidopsis thaliana remains subject to contradictory hypotheses. Results Here, we show that a highly organized cell death program is the final step of lateral root cap differentiation and that preparation for cell death is transcriptionally controlled by ANAC033/SOMBRERO. Precise timing of cell death is critical for the elimination of root cap cells before they fully enter the root elongation zone, which in turn is important in order to allow optimal root growth. Root cap cell death is followed by a rapid cell-autonomous corpse clearance and DNA fragmentation dependent on the S1-P1 type nuclease BFN1. Conclusions Based on these results, we propose a novel concept in plant development that recognizes programmed cell death as a mechanism for maintaining organ size and tissue homeostasis in the Arabidopsis root cap.